Association between prescription drugs and all‐cause mortality risk in the UK population - Morin, Jonas; Rolland, Yves; Bischoff‐Ferrari, Heike A.; Ocampo, Alejandro; Perez, Kevin (Aging cell, 2024)
Although most drugs currently approved are meant to treat specific diseases or symptoms, it has been hypothesized that some might bear a beneficial effect on lifespan in healthy older individuals, outside of their specific disease indication. Such drugs include, among others, metformin, SGLT2 inhibitors and rapamycin. Since 2006, the UK biobank has recorded prescription medication and mortality data for over 500′000 participants, aged between 40 and 70 years old. In this work, we examined the impact of the top 406 prescribed medications on overall mortality rates within the general population of the UK. As expected, most drugs were linked to a shorter lifespan, likely due to the life‐limiting nature of the diseases they are prescribed to treat. Importantly, a few drugs were associated with increased lifespans, including notably Sildenafil, Atorvastatin, Naproxen and Estradiol. These retrospective results warrant further investigation in randomized controlled trials. The UK Biobank has collected data on prescription medications and mortality for over 500,000 participants aged 40–70 years. We analyzed the effects of the top 406 prescribed medications on overall mortality rates in the general population. Most drugs were linked to a shortened lifespan, likely due to the life‐limiting nature of the diseases they are prescribed to treat. However, a few medications, notably Sildenafil, Atorvastatin, Naproxen, and Estradiol, were associated with increased lifespans.